Students' personal moral beliefs and ways of resolving moral problems - Agustin, Eric Datu (College of Education, University of the Philippines Diliman, 2016)
Ethical theories are key principles that determine right decisions and actions in morally problematic situations. Virtue ethics, which attracts persistent doubts and concerns, is the ethical framework for Values Education. As such, students' personal moral beliefs and related factors were examined, in comparison to the Philippine Department of Education's virtue ethics framework, for moral problem resolution. Using phenomenological method of data collection and analysis, the interviewees revealed the essential nature, structure, content, and meaning of their personal moral beliefs and related factors in resolving their moral problems. The phenomenological analysis of data uncovered six (6) themes (1) tapping personal traits characteristically; (2) exerting influence of factors from the local contexts, (3) lived experiencing of personal moral beliefs; (4) wielding personal moral beliefs effectively, (5) externalizing moral reflectiveness when utilizing PMBs, and, (6) following through moral consistency when applying PMBs. The emergence of a phenomenological theme indicated that students' personal moral beliefs and related factors guided them to resolve heuristically, reflectively and consistently their ethical problems. The significance of the overall findings includes the need to promote, enhance and understand more ethical principles in resolving moral problems prior to the teaching of the subject Values Education or Ethics. It has been concluded that there is a need to focus more on moral convictions and associated life aspects for the development of holistic societal members. The findings also imply the need for school authorities and capable individuals to guide adolescent students when making decisions.